2013
DOI: 10.1177/1538574413508827
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Perioperative Safety of Common Femoral Endarterectomy in the Endovascular Era

Abstract: Overall, CFE is tolerated well by the majority of patients with peripheral arterial disease. These results affirm the safety of CFE and can still be used as standard first-line therapy in most patients. Long-term results for endovascular interventions need to be studied to see whether high-risk patients that we identified for CFE would benefit more from an endovascular approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 32 publications
2
63
0
2
Order By: Relevance
“…20 Previous studies have demonstrated that RA may reduce the incidence of PLP in patients undergoing amputations, but the results have not been consistent. 21 O'Brien et al 11 have also demonstrated that the use of GA over locoregional anesthesia is an important predictor of early amputation failure. However, Recent publications, including a meta-analysis, have gathered positive evidence of the previously mentioned and other advantages of RA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Previous studies have demonstrated that RA may reduce the incidence of PLP in patients undergoing amputations, but the results have not been consistent. 21 O'Brien et al 11 have also demonstrated that the use of GA over locoregional anesthesia is an important predictor of early amputation failure. However, Recent publications, including a meta-analysis, have gathered positive evidence of the previously mentioned and other advantages of RA.…”
Section: Discussionmentioning
confidence: 99%
“…However, these data largely consist of patients undergoing orthopedic, urologic, general surgical, and vascular surgery procedures. 5,11,21 We were able to identify only a limited number of studies evaluating the effects of anesthesia choice specifically in LEA procedures such as BKAs or above-knee amputations (AKAs). In fact, only 1 study used the NSQIP database to study outcomes in this surgical population, but it has several methodological limitations as described below.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Siracuse et al investigated a total of 1,513 patients undergoing elective CFE, and found that 30-day postoperative mortality was 1.5%. 19 Postoperative morbidities included cardiac (1.0%), pulmonary (1.9%), renal (0.4%), urinary tract infection (1.7%), thromboembolic (0.5%), neurologic (0.4%), sepsis (2.7%), superficial (6.3%), and deep surgical site complications (2.0%); at least 1 complication, including major or minor, was seen in 7.9% of the patients. There were 2 perioperative deaths in the present study: 1.7% in the overall group and 4.7% in the CLI groups.…”
Section: Kuma S Et Almentioning
confidence: 99%
“…This alone can also provide relief for patients with distal disease, particularly those with rest pain 44. A review of patients undergoing isolated elective common femoral endarterectomy showed a 30-day mortality rate of 1.5% 45. Wound infection was the most common postoperative complication divided into superficial (6.3%) and deep (2.0%).…”
Section: Adjunctsmentioning
confidence: 99%